Tacitus' annals - Mellor, Ronald (Oxford ; New York : Oxford University Press, 2010)
Tacitus' Annals is the central historical source for first-century C.E. Rome. It is prized by historians since it provides the best narrative material for the reigns of Tiberius, Claudius, and Nero, as well as a probing analysis of the imperial system of government. But the Annals should be seen as far more than an historical source, a mere mine for the reconstruction of the facts of Roman history. While the Annals is a superb work of history, it has also become a central text in the western literary, political, and even philosophical traditions - from the Renaissance to the French and America.
The creation of a political historian -- The historian and his sources -- Ethnic prejudice in Tacitus -- Ut pictura poesis : the visual representation of history -- Freedom and censorship -- A Tiberian narrative -- Consorts of the Caesars -- Courtiers on the Palatine : the familia of the Caesars -- Performances at the court : the reigns of Claudius and Nero -- The importance of Tacitus' Annals -- The Julio-Claudian family (genealogy) -- Map of the Roman Empire -- Prominent persons.
Includes bibliographical references (pages 239-244) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Tacitus, Cornelius; Tacitus, Cornelius -- Criticism and interpretation; Tacitus, Cornelius; Annales (Tacitus, Cornelius); Rome -- Historiography; HISTORY -- Ancient; Historiography; Rome (Empire); Criticism, interpretation, etc